2007
DOI: 10.1128/aac.01458-06
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Isolated Mycobacterium tuberculosis Fatty Acid Synthase I by Pyrazinamide Analogs

Abstract: An analog of pyrazinamide (PZA), 5-chloropyrazinamide (5-Cl-PZA), has previously been shown to inhibit mycobacterial fatty acid synthase I (FASI). FASI has been purified from a recombinant strain of M. smegmatis (M. smegmatis ⌬fas1 attB::M. tuberculosis fas1). Following purification, FASI activity and inhibition were assessed spectrophotometrically by monitoring NADPH oxidation. The observed inhibition was both concentration and structure dependent, being affected by both substitution at the 5 position of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 30 publications
(36 reference statements)
3
62
0
Order By: Relevance
“…Strains were grown to mid-log phase (OD 600 , 0.5), cells were harvested by centrifugation (3,450 ϫ g; 10 min; 4°C), resuspended to an OD 600 of 0.2 in 10 ml 7H9 medium (pH 5.1) containing 2.5 mg ml Ϫ1 PZA, and incubated for 2 h at 37°C. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetate (1 Ci ml Ϫ1 ) was added, and the cultures were incubated for an additional 2 h. Cells were harvested by centrifugation (3,450 ϫ g; 10 min; 4°C). Fatty acid preparation and analysis were performed as previously described (28).…”
Section: Construction Of Mycobacterial Mutant Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains were grown to mid-log phase (OD 600 , 0.5), cells were harvested by centrifugation (3,450 ϫ g; 10 min; 4°C), resuspended to an OD 600 of 0.2 in 10 ml 7H9 medium (pH 5.1) containing 2.5 mg ml Ϫ1 PZA, and incubated for 2 h at 37°C. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetate (1 Ci ml Ϫ1 ) was added, and the cultures were incubated for an additional 2 h. Cells were harvested by centrifugation (3,450 ϫ g; 10 min; 4°C). Fatty acid preparation and analysis were performed as previously described (28).…”
Section: Construction Of Mycobacterial Mutant Strainsmentioning
confidence: 99%
“…Based on the pK a and acidic-pH dependence of PA, it has been suggested that this weak acid works via a proton ionophore-type mechanism that directly causes uncoupling of the cellular membrane potential (22,25). However, it is important to note that PZA and many of its derivatives, such as n-propyl pyrazinoate, PA, and 5-Cl PZA, inhibit mycobacterial type 1 fatty acid synthase (FAS I) in whole-cell and cell-free assays (14,27). Moreover, synthetic overexpression of mycobacterial FAS I in M. smegmatis confers resistance to 5-Cl PZA (26).…”
mentioning
confidence: 99%
“…PZA and related analogs have also demonstrated activity against other Mycobacterium spp. (9,21,27). In myco-bacteria, we found that PZA inhibits the enzyme fatty acid synthase I (FASI) (33) by competitive inhibition of a NADPH binding site (25).…”
mentioning
confidence: 99%
“…PZA is a sterilizing drug that efficiently kills populations of Mycobacterium tuberculosis residing in acidic environments, as found during active inflammation (1,7,10,11,20,21,28,32). Despite the importance of PZA, no cellular target proteins have been clearly identified (4,23,30,41), and its mechanism of action is probably the least understood among all first-and second-line antituberculosis drugs. A better understanding of PZA action may help in development of new drugs to further shorten tuberculosis treatment.…”
mentioning
confidence: 99%